Simulating background settings during spoken and written sentence comprehension - Horchak, O. V. (2022)
Previous findings from the sentence-picture verification task demonstrated that comprehenders simulate visual information about intrinsic attributes of described objects. Of interest is whether comprehenders may also simulate the setting in which an event takes place, such as, for example, the light information. To address this question, four experiments were conducted in which participants (total N = 412) either listened to (Experiment 1) or read (Experiment 3) sentences like “The sun is shining onto a bench” followed by a picture with the matching object (bench) and either the matching lighting condition of the scene (sunlit bench against the sunlit background) or the mismatching one (moonlit bench against the moonlit background). In both experiments, response times (RTs) were shorter when the lighting condition of the pictured scene matched the one implied in the sentence. However, no difference in RTs was observed when the processing of spoken sentences was interfered with visual noise (Experiment 2). Specifically, the results showed that visual interference disrupted incongruent visual content activated by listening to the sentences, as evidenced by faster responses on mismatching trials. Similarly, no difference in RTs was observed when the lighting condition of the pictured scene matched sentence context, but the target object presented for verification mismatched sentence context (Experiment 4). Thus, the locus of simulation effect is on the lighting representation of the target object rather than the lighting representation of the background. These findings support embodied and situated accounts of cognition, suggesting that comprehenders do not simulate objects independently of background settings.